Dudley Murphy, Hollywood Wild Card - Delson, Susan (Book collections on Project MUSE., 2006)
Dudley Murphy (1897-1968) was one of early Hollywood's most intriguing figures. Active from the 1920s through the 1940s, Murphy was one of the industry's first independents and a guiding intelligence behind some of the key films in early twentieth-century cinema. In the first full-length biography of Murphy, Susan Delson gives full rein to an American original whose life was as audacious as his films.